The Role of Chitinase-3-like Protein-1 (YKL40) in the Therapy of Cancer and Other Chronic-Inflammation-Related Diseases - Ming-Cheng Chang; Chun-Tang Chen; Ping-Fang Chiang; Ying-Cheng Chiang (MDPI AG, 2024)
Chitinase-3-like protein-1 (CHI3L1), also known as YKL40, is a glycoprotein that belongs to the chitinase protein family. It is involved in various biological functions, including cell proliferation and tissue remodeling, with inflammatory and immunomodulatory capabilities. Several studies have shown that CHI3L1(YKL40) is upregulated in various diseases, such as cancer, asthma, and inflammatory bowel disease, among others. Although the expression level of CHI3L1(YKL40) is associated with disease activity, severity, and prognosis, its potential as a therapeutic target is still under investigation. In this review, we summarize the biological functions, pathological roles, and potential clinical applications of specific inhibitors and targeted therapies related to CHI3L1(YKL40).